Charged triazole cross-linkers for hyaluronan-based hybrid hydrogels - Martini, Maike Stefanie; Mundinger, Patricia; Schädel, Nicole; Minsky, Burcu Baykal; Kirchhof, Manuel; Scholl, Sebastian; Southan, Alexander; Tovar, Günter; Böhm, Heike; Laschat, Sabine (Materials, 2016)
Polyelectrolyte hydrogels play an important role in tissue engineering and can be produced from natural polymers, such as the glycosaminoglycan hyaluronan. In order to control charge density and mechanical properties of hyaluronan-based hydrogels, we developed cross-linkers with a neutral or positively charged triazole core with different lengths of spacer arms and two terminal maleimide groups. These cross-linkers react with thiolated hyaluronan in a fast, stoichiometric thio-Michael addition. Introducing a positive charge on the core of the cross-linker enabled us to compare hydrogels with the same interconnectivity, but a different charge density. Positively charged cross-linkers form stiffer hydrogels relatively independent of the size of the cross-linker, whereas neutral cross-linkers only form stable hydrogels at small spacer lengths. These novel cross-linkers provide a platform to tune the hydrogel network charge and thus the mechanical properties of the network. In addition, they might offer a wide range of applications especially in bioprinting for precise design of hydrogels.
Gesehen am 11.05.2020